Gamma-radiation Induced Changes on Several Reproductive Potentials in Callosobruchus chinensis (L.) and C. Maculatus (F.) (Coleoptera: Bruchidae) (Bangladesh Journal of Genetics and Biotechnology, 2008)
No abstract available.Key words: Callosobruchus ; reproductive potential; gamma radiation; probit mortality and sterility responses Bangladesh j. genet. biotechnol. 6 (1&2): 23-28, 2005 (June & December)